Electrochemical Oxidation‐Induced Oxyphosphorylation of Alkenes and Alkynes with Water via Hydrogen Atom Transfer. Issue 16 (14th July 2022) - Yang, Jianjing; Sun, Xue; Yan, Kelu; Sun, Hongzhao; Sun, Shuai; Jia, Xiaoyu; Zhang, Fanjun; Wen, Jiangwei
Abstract: A metal‐ and exogenous‐oxidant‐free oxidation‐induced oxyphosphorylation of alkenes and alkynes with water for β‐ketophosphonates has been developed through the radical coupling under electrochemical conditions. This protocol is compatible with a wide range of alkenes, alkynes, and diarylphosphorus derivatives, and enables the gram‐scale synthesis of β‐ketophosphonates. The mechanistic study revealed that the P radicals were generated via hydrogen atom transfer (HAT) event jointly mediated by tetrabutylammonium acetate and anode oxidation process. Abstract :